Do teleoncology models of care enable safe delivery of chemotherapy in rural towns?. Issue 10 (16th November 2015) - Chan, Bryan A; Larkins, Sarah L; Evans, Rebecca; Watt, Kerrianne; Sabesan, Sabe
Abstract: Objectives: To compare the dose intensity and toxicity profiles for patients undergoing chemotherapy at the Townsville Cancer Centre (TCC), a tertiary cancer centre in northern Queensland, with those for patients treated in Mount Isa, supervised by the same medical oncologists via teleoncology. Design: A quasi‐experimental design comparing two patient groups. Setting: TCC and Mount Isa Hospital, which both operate under the auspices of the Townsville Teleoncology Network (TTN). Participants: Eligible patients who received chemotherapy at TCC or Mt Isa Hospital between 1 May 2007 and 30 April 2012. Intervention: Teleoncology model for managing cancer patients in rural towns. Main outcome measures: Dose intensity (doses, number of cycles and lines of treatment) and toxicity rates (rate of serious side effects, hospital admissions and mortality). Results: Over 5 years, 89 patients received a total of 626 cycles of various chemotherapy regimens in Mount Isa. During the same period, 117 patients who received a total of 799 cycles of chemotherapy at TCC were eligible for inclusion in the comparison group. There were no significant differences between the Mount Isa and TCC patients in most demographic characteristics, mean numbers of treatment cycles, dose intensities, proportions of side effects, and hospital admissions. There were no toxicity‐related deaths in either group. Conclusion: It appears safe to administer chemotherapy in rural towns under the supervision of medical oncologists from larger centres via teleoncology, provided that rural health care resources and governance arrangements are adequate.